2001
DOI: 10.1108/eum0000000005637
|View full text |Cite
|
Sign up to set email alerts
|

The right stuff: understanding cultural differences in leadership performance

Abstract: A study was conducted that examined which managerial skill dimensions were critical for effective leadership for managers in the USA and seven European countries. The results suggested more similarities than differences across countries. Specifically, a core group of two skill dimensions emerged as critical for effective leadership across countries and operationalizations of criticality. These dimensions were analyze issues and drive for results. However, results did differ depending on how criticality was ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…In another study, managers' ratings of managerial skills of U.S. managers and those in seven European countries were found to be more similar than different (Robie et al, 2001). Sanyal and Guvenli (2004) asked managers in Israel, Slovenia, and the United States to rate their perception of the characteristics and abilities of managers that contribute to the success of their firm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, managers' ratings of managerial skills of U.S. managers and those in seven European countries were found to be more similar than different (Robie et al, 2001). Sanyal and Guvenli (2004) asked managers in Israel, Slovenia, and the United States to rate their perception of the characteristics and abilities of managers that contribute to the success of their firm.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers in the cross-cultural leadership literature have suggested that globalization and widespread management education programs (e.g., MBA programs) that reflect Western theories of leadership are creating cultural convergence in the behaviors expected of successful managers and leaders (House et al, 1997). Responsibilities and challenges of managers leading in the 21st-century global economy may require similar management competencies that are unaffected by culture (Robie, Johnson, Nilsen, & Hazucha, 2001). In one phase of the GLOBE project, researchers investigated the extent to which specific leader attributes and behaviors are universally endorsed as contributing to effective leadership.…”
Section: Discussionmentioning
confidence: 99%
“…That 77.78% (n ¼ 21) behavioural categories are generalized across two sectors and three countries lends support to those who theorize the 'universalistic' nature of perceived managerial/leadership effectiveness (see Robie et al 2001). It follows that the concept of national culture should be used with more caution in management/leadership studies (McSweeney 2009).…”
Section: Deducing a Taxonomy Of Perceived Managerial And Leadership Ementioning
confidence: 78%
“…Being self-centred and malevolent was perceived as detrimental for being an effective leader. In a similar vein, in a study among US and European managers, Robie et al (2001) found that a drive for results and analysing issues effectively were the best predictors for effective managerial performance. Lesley and Van Velsor (1998) found that US and European managers perceive managerial effectiveness as having personal influence, being cooperative, and accepting rules and procedures set by an external authority.…”
Section: Introductionmentioning
confidence: 88%